Expression and Activation of Toll-Like Receptor 9 in Dengue Virus Infection: A Scoping Review - Safari Wahyu Jatmiko; Riandini Aisyah (Universitas Muhammadiyah Surakarta, 2023)
Toll-like receptors (TLR) are essential to pathogen recognition to activate innate immunity. TLR2, 3, 4, 6, 7, 8, and 9 are involved in immunity to dengue virus. The involvement of TLR9, known to recognize CpG DNA, in dengue virus (DVI) infection, an RNA virus, is unusual. We hypothesize that there is an elevated expression and activation of TLR9 through specific mechanisms in DVI. A scoping review was carried out to collect articles that have been written regarding this topic. Article searches were carried out on the PubMed (Medline), Proquest, EBSCO, and Google Scholar databases with inclusion criteria: articles in the form of research results using human subjects or human cells, conducted from 2013 to 2023, in English, and can be accessed in full -text. Gray articles, books, and review articles were excluded from the study. The literature search results found 821 articles, with eight articles meeting the criteria. Based on mapping, synthesis, and analysis of the articles obtained, it was found that there was increased expression and activation of TLR9 in the DVI due to the release of mtDNA.